A Pigovian Approach to Liquidity Regulation - Enrico Perotti; Javier Suarez (Tinbergen Institute, 2011)
This paper discusses liquidity regulation when short-term funding enables credit growth but generates negative systemic risk externalities. It focuses on the relativemerit of price versus quantity rules, showing how they target different incentives for risk creation.When banks differ in credit opportunities, a Pigovian tax on short-term funding is efficient in containing risk and preserving credit quality, while quantity-based fundingratios are distorsionary. Liquidity buffers are either fully ineffective or similar to a Pigovian tax with deadweight costs. Critically, they may be least binding when excess credit incentives are strongest.When banks differ instead mostly in gambling incentives (due to low charter valueor overconfidence), excess credit and liquidity risk are best controlled with net fundingratios. Taxes on short-term funding emerge again as efficient when capital or liquidityratios keep risk shifting incentives under control. In general, an optimal policy shouldinvolve both types of tools.
Keywords: G21; G28; 330; Systemic risk; Liquidity risk; Liquidity requirements; Liquidity risk levies; Macroprudential regulation; Kreditrisiko; Systemrisiko; Bankenliquidität; Bankenregulierung; Internalisierung externer Effekte; Theorie